Intestinal mucus barrier: a missing piece of the puzzle in food allergy. Issue 1 (January 2022) - Parrish, Amy; Boudaud, Marie; Kuehn, Annette; Ollert, Markus; Desai, Mahesh S.
Abstract : The prevalence of food allergies has reached epidemic levels but the cause remains largely unknown. We discuss the clinical relevance of the gut mucosal barrier as a site for allergic sensitization to food. In this context, we focus on an important but overlooked part of the mucosal barrier in pathogenesis, the glycoprotein-rich mucus layer, and call attention to both beneficial and detrimental aspects of mucus–gut microbiome interactions. Studying the intricate links between the mucus barrier, the associated bacteria, and the mucosal immune system may advance our understanding of the mechanisms and inform prevention and treatment strategies in food allergy. Highlights: The sudden rise in food allergy over recent decades has led to various theories including the role of environmental factors in sensitization. Gastrointestinal (GI) mucins have recently been implicated in maintaining gut homeostasis: mice lacking a functional mucus layer ( Muc2 −/− mice) are more susceptible to colitis and GI infection, in addition to severe oral tolerance breakdown following sensitization with a food allergen. Thus, further research will be necessary to understand how functional changes in O -glycosylated mucins might contribute to the epidemic of food allergy. Factors including reduced consumption of dietary fiber and/or increased consumption of food additives are emerging as key determinants of altered mucus barrier function and mucin−gut microbiota interactions which appear to play an important role in regulating food allergy.